Detection and genetic characterization of porcine astroviruses in piglets with and without diarrhea in Thailand - Kattareeya Kumthip (2018)
© 2018 Springer-Verlag GmbH Austria, part of Springer Nature Porcine astrovirus (PAstV) is widely distributed and highly prevalent among pigs, nevertheless its clinical significance remains unclear as it can be detected in both diarrheic and in healthy pigs. Information about the prevalence, clinical significance and molecular characterization of PAstV in Thailand is not available. This study investigated the prevalence of PAstV in 488 fecal samples collected from piglets with and without diarrhea in 28 pig farms in northern and central parts of Thailand using RT-PCR. The overall prevalence of PAstV infection was 6.5% (32/488), of which 21/251 (8.4%) were in diarrheic and 11/237 (4.6%) were in healthy pigs. Of 32 positive samples, 46.9% were positive for PAstV alone whereas 53.1% were co-infected with porcine group A rotavirus (PRVA). A phylogenetic analysis of the partial RNA-dependent RNA polymerase/capsid genes revealed two lineages of PAstV strains detected in this study. PAstV4 was the most dominant genotype (92%), followed by PAstV2 (8%). This study revealed for the first time that PAstV4 and PAstV2 were circulating in Thailand with PAstV4 as the most dominant genotype in pig herds in northern and central parts of Thailand.